Movimento, educação escolar indígena e os processos de (re)afirmações dos Kambeba na região do médio solimões-AM. - Macedo, Magiles de Souza (2021)
The present work aimed to investigate the formation of the indigenous movement and the role of Indigenous School Education in the processes of (re)affirmation of the ethnic identities of the Kambeba, in the Middle Solimões/AM region. The same is based on the qualitative approach, having as methodological procedure the bibliographical and documental research. The theoretical foundation was based on Bartolomé (2006), Porro (1992), Barth (1995), Fontella (2020), Cunha (1992), Gondin (2007), Maciel (2007), Monteiro (1999), Santos (19993), Sampaio (2012), Faulhaber (1998), Luciano (2006), Oliveira (2004), among others. The results show that indigenous populations were not passive social actors in the colonization process and other moments in history. At all stages of the process of meeting the non-indigenous, the indigenous people promoted actions that denote their protagonism. In the second half of the 20th century, the indigenous movement articulated different indigenous groups in Brazil. This movement was political, as these populations began to claim rights such as health, land and education. This movement was ethnic in nature, as it allowed for the affirmation of ethnic groups that remained silent due to the colonization process. In the Middle Solimões region, effective participation in the indigenous movement resulted in the ethnic affirmation of the Kambeba. In the last two decades, the Kambeba of the Boará and Boarazinho communities, located on the left bank of the Solimões River, municipality of Tefé/AM, have continued the process of affirmation amid the influences of the so-called dominant society. These populations, even without the support of local government entities, promote Indigenous School Education based on their own learning processes that contribute to the strengthening of their identities and here we analyze the experience. Thus, the trajectory of the Kambeba reveals only one of the facets of the countless indigenous groups that are part of the immense mosaic of populations that inhabit the Amazon and that need to be known not only by academia, but by society as a whole.